Assessment Of An Acrylic Polymer On The Properties Of Soil-Cement - Wong, Khien Ngie (2003)
The aim of this study is to compare the performance of Soil Cement with a manufactured polymer in order to examine the physical properties of the stabilized materiaL The study determine strength, durability, chemical analysis, mineralogical study, microstructural investigation and, computer modeling, CHEVPC. The laterite soil named Serdang series was used as a fundamental control material for this study. Normal Portland cement and polymer were used as stabilizing agents. Analysis of Variance (ANOVA) design and Tukey test were used for the unconfined compression strength data between the curing periods and between cement and polymer content. The study showed significant difference (p < 0.05) in the amount for 8% cement with 1 0% polymer (SCP8 1 0) between the curing periods, between cement content; and between polymer content .